Imaginário e emoção: três campanhas publicitárias da Natura Cosméticos - Galhardi, Luciana Pletsch (2012)
In the face of a little explored area and distrust of certainty, we launched the advertising communication a question: how to configure the media advertising business that uses the persuasive emotional appeal as an alternative? To this end, we choose the company Natura Cosméticos as an object of study, and released the following research problems: what are the characteristics of this type of advertising? What are the elements present in the speech intended to thrill? And how advertising contributes to create an imaginary? Seeking some understanding, explore emotional advertising in contemporary everyday life, its use by the company, and its impact in shaping the postmodern imagination. Through a plural methodological strategy that tries to cope with everyday, we analyzed three campaigns of the company: Well Being Well ; 40 Years ; and Happy Brazil for You . Following the theoretical understanding of sociology and semiotic analysis, we made a thorough analysis of the data in an attempt to provide answers to the questions raised by interpreting the light of theories.